2020
DOI: 10.3390/plants9040478
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Chloroplast Genome of Two Important Annual Clover Species, Trifolium alexandrinum and T. resupinatum: Genome Structure, Comparative Analyses and Phylogenetic Relationships with Relatives in Leguminosae

Abstract: Trifolium L., which belongs to the IR lacking clade (IRLC), is one of the largest genera in the Leguminosae and contains several economically important fodder species. Here, we present whole chloroplast (cp) genome sequencing and annotation of two important annual grasses, Trifolium alexandrinum (Egyptian clover) and T. resupinatum (Persian clover). Abundant single nucleotide polymorphisms (SNPs) and insertions/deletions (In/Dels) were discovered between those two species. Global alignment of T. alexandrinum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 63 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…Both of A. sagittifolius and A. esculentus had six types SSRs, but A. moschatus and A. manihot did not contain hexanucleotides. Most SSRs were distributed in LSC region and intergenic region, and the identified SSRs in Abelmoschus revealed that A/T and AT/TA were the most abundant in mononucleotide and dinucleotide SSRs respectively, which agreed with the majority of plant family [24]. Moreover, repeat sequences was lower in A. esculentus compared https://doi.org/10.1371/journal.pone.0242591.g007…”
Section: Ssrs and Repeat Sequences In Abelmoschusmentioning
confidence: 77%
See 1 more Smart Citation
“…Both of A. sagittifolius and A. esculentus had six types SSRs, but A. moschatus and A. manihot did not contain hexanucleotides. Most SSRs were distributed in LSC region and intergenic region, and the identified SSRs in Abelmoschus revealed that A/T and AT/TA were the most abundant in mononucleotide and dinucleotide SSRs respectively, which agreed with the majority of plant family [24]. Moreover, repeat sequences was lower in A. esculentus compared https://doi.org/10.1371/journal.pone.0242591.g007…”
Section: Ssrs and Repeat Sequences In Abelmoschusmentioning
confidence: 77%
“…Raw reads of three Abelmoschus species were filtered using the software NGSQCToolkit V2.3.3. In order to reduce the complexity of sequence assembly, filtered reads were compared with the chloroplast genome database built by Genepioneer Biotechnologies (Nanjing, China) using Bowtie2 V2.2.4, and sequences on the alignment was used as the chloroplast genome sequence of samples [24]. Seed sequence was obtained by software SPAdes v3.10.1, and contigs was acquired by kmer iterative extend seed.…”
Section: Chloroplast Genome Assembly and Annotationmentioning
confidence: 99%
“…Fabaceae is considering a large and economically vital family of flowering plants which is usually known as the legume family [1][2][3]. The Fabaceae family, which includes 730 genera more than 19,400 species, is the second-largest family of medicinal plants and the third largest family of flowering plants, with over 490 medicinal plant species [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The matK gene (1500 bp in length), located inside the intron of the trnK and codes for protein maturase, which is involved in Group-II intron splicing. This gene has a high substitution rate [3], a huge fraction of variance in nucleic acid levels between the first and second codon positions, a low transition and or/transversion ratio, and mutationally conserved areas. Previous data were utilized to identify the molecular markers, which were used to identify the genus/species of these taxa, to provide valuable information for both conventional and molecular studies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Information gained from complete chloroplast (cp) genome sequences and structure can explain the variation among plant species and provide valuable genomic information for the phylogenetics study (Xiong et al. 1975 ). But there is still only a few complete cp genome that was characterized for the species in C. tomentosa .…”
mentioning
confidence: 99%